Assessing the effect of current account and currency crises on economic growth - Christian Aßmann (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2011)
Several empirical studies are concerned with measuring the effect of currency and current account crises on economic growth. Using different empirical models this paper serves two aspects. It provides an explicit assessment of country specific factors influencing the costs of crises in terms of economic growth and controls via a treatment type model for possible sample selection governing the occurrence of crises in order to estimate the impact on economic growth correctly. The applied empirical models allow for rich intertemporal dependencies via serially correlated errors and capture latent country specific heterogeneity via random coefficients. For accurate estimation of the treatment type model a simulated maximum likelihood approach employing efficient importance sampling is used. The results reveal significant costs in terms of economic growth for both crises. Costs for reversals are linked to country specific variables, while costs for currency crises are not. Furthermore, shocks explaining current account reversals and growth show strong significant positive correlation.
Keywords: F32; C15; C23; C33; O10; 330; Currency crises; Current account reversals; Treatment Model; Discrete dependent variable; Efficient Importance Sampling; Panel Data